Effort of Bhabinkamtibmas in Preventing the Development of Radicalism through Sambang in the Jurisdiction of the Temanggung Police - Ibnu Irsyady (Tanggon Kosala, 2023)
The background of this research is that there are still radical groups who have not been able to accept Pancasila as the sole principle of nationhood and statehood and have broken the unity of the nation by inciting the people. The National Police, especially the Temanggung Police Station, must immediately take proportional and professional steps. One of the preventive measures used by the National Police is a pre-emptive effort with the Binmas technical function as one of the executors. One of the methods of delivering safety messages to the public is through the sambang Bhabinkamtibmas . The purpose of this research was to determine the competence of Bhabinkamtibmas and the implementation of sambang by Bhabinkamtibmas in preventing the development of radicalism in Temanggung Regency. The research method used is to use a qualitative approach. Data collection techniques by conducting interviews, observation, and document study. The use of POAC management theory by George R Terry as an analytical knife for the implementation of sambang activities, as well as competency theory by Busro to analyze the competencies of Bhabinkamtibmas. The results showed that the competence possessed by Bhabinkamtibmas and the implementation of sambang activities were not in accordance with standard operating procedures in accordance with Perkap Number 7 of 2021 concerning Bhabinkamtibmas and the 2018 Bhabinkamtibmas smart book. There were factors that influenced the initial conditions so that the implementation of Bhabinkamtibmas activities did not go well . From the results of this study, the solution to the problem given to Bhabinkamtibmas and Sat Binmas Polres Temanggung is to pay more attention to the competence of Bhabinkamtibmas and evaluate the implementation of active sambang in preventing the spread of radicalism in Temanggung Regency.